Identification of public place attributes using mean-end chain research model - Bentalhoda Fooladivanda, 1986-; Mahmud Mohd. Jusan; Fakulti Alam Bina (2012)
Thesis (Sarjana Sains (Rekabentuk Bandar)) - Universiti Teknologi Malaysia, 2012